Visual basic electronic display / Rosli Mansor - Mansor, Rosli (1999)
An electronic display is used to display information in the form of alphanumeric characters or graphical sign. The information can be easily change to suit its purpose for public view. This projek ilmiah presents a visual basic 6.0 (VB) program for moving message electronic display. The VB software controls the signal output to the display through the parallel port of personal computer. The text message is typed in the VB input text box. This technique is simple and provides a user-friendly interface to display information on the moving message display unit.